The Role of Profitability on Firm Value Using Corporate Social Responsibility as a Moderation Variable - Susandya, Anak Agung Putu Gede Bagus Arie; Sunarwijaya, I Ketut (International Journal on Social Science, Economics and Art, 2025)
The aim of this research is to examine the effect of profitability on company value with disclosure of corporate social responsibility as a moderating variable in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. The population of this research is manufacturing companies in the consumer goods industry sector listed on the IDX for 2020 - 2022. The sample in this study was 36 manufacturing companies in the consumer goods industry sector which were determined based on the purposive sampling method. The data analysis used to test the hypothesis is MRA (Moderated Regression Analysis). Based on the research results, it shows that profitability has a positive effect on company value. Meanwhile, Corporate Social Responsibility is able to moderate the relationship between Profitability and Company Value in a negative direction. This means that the profitability variable with disclosure of Corporate Social Responsibility as moderation weakens profitability on company value. Future research can develop research by using other variables or adding other variables that are more relevant to company value, such as company size and dividend policy.